2013
DOI: 10.1186/1758-5996-5-34
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent differences in diabetes and acute hyperglycemia between men and women with ST-elevation myocardial infarction: a cohort study

Abstract: BackgroundBoth acute hyperglycemia as diabetes results in an impaired prognosis in ST-elevation myocardial infarction (STEMI) patients. It is unknown whether there is a different prevalence of diabetes and acute hyperglycemia in men and women within age-groups.MethodsBetween 2004 and 2010, 4640 consecutive patients (28% women) with STEMI, were referred for primary PCI. Patients were stratified into two age groups, < 65 years (2447 patients) and ≥65 years (2193 patients). Separate analyses were performed in 390… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The 13 trials included in the meta-analysis were summarized in Table 1 . Seven of the selected cohort studies [ 8 , 13 18 ] reported both the early and late outcome events, whereas 5 studies [ 19 23 ] only reported the early outcome events and one study [ 24 ] only report the late outcome event. Within the 13 trials, the mean age for non-diabetic participants ranged from 55 to 65 years, and the proportion of men in majority of the studies ranged from 68% to 88%, while 1 study reported mortalities stratified by sex [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 13 trials included in the meta-analysis were summarized in Table 1 . Seven of the selected cohort studies [ 8 , 13 18 ] reported both the early and late outcome events, whereas 5 studies [ 19 23 ] only reported the early outcome events and one study [ 24 ] only report the late outcome event. Within the 13 trials, the mean age for non-diabetic participants ranged from 55 to 65 years, and the proportion of men in majority of the studies ranged from 68% to 88%, while 1 study reported mortalities stratified by sex [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is common among the middle-aged and elderly individuals. 17 In recent years, STEMI incidence and mortality have been increasing year by year. Recently, it is not unusual for many young patients to have an acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“… 36 In addition, studies on this issue conducted in elderly patients with AMI are scarce. 37 For example, a meta-analysis including six cohort studies reported that elevated admission glucose (≥6.1–11.1 mmol/L) was significantly associated with short-term mortality in patients with STEMI without diabetes (RR 4.38; 95% CI 3.23 to 5.94). 38 In another study conducted in patients with NSTEMI undergoing PCI, admission blood glucose was a predictor of 30-day major adverse cardiovascular events (MACE), irrespective of diabetes status.…”
Section: Discussionmentioning
confidence: 99%